Management of Lower Urinary Tract Symptoms Attributed to Benign Prostatic Hyperplasia: AUA GUIDELINE PART I-Initial Work-up and Medical Management - Lerner, Lori B.; McVary, Kevin T.; Barry, Michael J.; Bixler, Brooke R.; Dahm, Philipp; Das, Anurag Kumar; Gandhi, Manhar C.; Kaplan, Steven A.; Kohler, Tobias S.; Martin, Leslie; Parsons, J. Kellogg; Roehrborn, Claus G.; et al. (The Journal of urology, 2021)
Purpose:Benign prostatic hyperplasia (BPH) is a histologic diagnosis describing proliferation of smooth muscle and epithelial cells within the prostatic transition zone. The prevalence and severity of lower urinary tract symptoms (LUTS) in aging men are progressive and impact the health and welfare of society. This revised Guideline provides a useful reference on effective evidence-based management of male LUTS/BPH. See the accompanying algorithm for a summary of the procedures detailed in the Guideline (figures 1 and 2Figure 1.Basic Management of LUTS in Men AlgorithmFigure 2.Trial of Medical Therapy Algorithm).Materials and Methods:The Minnesota Evidence Review Team searched Ovid MEDLINE, Embase, Cochrane Library, and AHRQ databases to identify eligible English language studies published between January 2008 and April 2019, then updated through December 2020. Search terms included Medical Subject Headings (MeSH) and keywords for pharmacological therapies, drug classes, and terms related to LUTS or BPH. When sufficient evidence existed, the body of evidence was assigned a strength rating of A (high), B (moderate), or C (low) for support of Strong, Moderate, or Conditional Recommendations. In the absence of sufficient evidence, information is provided as Clinical Principles and Expert Opinions (table 1Table 1.AUA Nomenclature Linking Statement Type to Level of Certainty, Magnitude of Benefit or Risk/Burden, and Body of Evidence Strength).Results:Nineteen guideline statements pertinent to evaluation, work-up, and medical management were developed. Appropriate levels of evidence and supporting text were created to direct both primary care and urologic providers towards streamlined and suitable practices.Conclusions:The work up and medical management of BPH requires attention to individual patient characteristics, while also respecting common principles. Clinicians should adhere to recommendations and familiarize themselves with standards of BPH management.